1, 3‐Diamino‐2‐propanol or 2‐aminoethanethiol modified active layer of thin‐film composite forward osmosis membrane. Issue 36 (7th May 2019) - Sun, Jiajin; Hu, Xuhui; Huang, Yangbo; Peng, Ruichao; Luo, Yunbai; Yu, Ping
ABSTRACT: This work proposes three easy and effective methods to improve the density of the active layer of the thin‐film composite (TFC) forward osmosis (FO) membrane. Amino groups are introduced to the polyamide layer to react with the exposed acid chloride groups after a small molecule of 1, 3‐diamino‐2‐propanol (DH) or 2‐aminoethanethiol (AE) or DH–AE being introduced. This may lead to a higher degree of crosslinking and form a more complex and networked aggregate structure. In this work, three modified membranes are successfully prepared, and a series of characterizations are carried out. The result is that all methods can improve the density of the active layer and increase the salt rejection without adversely affecting the selectivity. The hydrophilicity of the TFC‐DH film is significantly improved, the reverse salt flux of the TFC‐AE film is remarkably improved, and the effect of the TFC‐DH–AE film is between the TFC‐DH film and the TFC‐AE film. Therefore, the method of adding a small molecular material can increase the degree of polymerization. The method of introducing an inorganic element provides a valuable solution for designing and developing a novel and efficient FO film, which is simple and easy to be operated. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47923. Abstract : Morphological changes of three modified membranes.